af(x) = ax = |
1
1
|
x |
af(x) = ax2 = |
1
1
|
x2 |
af(x) = a√ x = |
1
1
|
√ x |
af(x) = a |
1
x
|
= |
1
1
|
1
x
|
af(x) = ax3 = |
1
1
|
x3 |
af(x) = a | = |
1
1
|
af(x) = a2x = |
1
1
|
2x |
af(x) = a10x = |
1
1
|
10x |
af(x) = aex = |
1
1
|
ex |
af(x) = a|x| = |
1
1
|
|x| |
af(x) = alog2x = |
1
1
|
log2x |
af(x) = alogx = |
1
1
|
logx |
af(x) = alnx = |
1
1
|
lnx |
f(x) = x | |||
|
f(x) = √ x | |||
|
|
|||
|
f(x) = |x| | ||||
|
f(x) = logx | ||||
|
f(x) = lnx | ||||
|
f(bx) = bx = |
1
1
|
x |
f(bx) = (bx)2 = ( |
1
1
|
x)2 |
f(bx) = √ bx = |
1
1
|
x |
f(bx) =
|
1
bx
|
= |
1
|
f(bx) = (bx)3 = ( |
1
1
|
x)3 |
f(bx) = | = |
1
1
|
x |
f(bx) = 2bx = 2 |
1
1
|
x |
f(bx) = 10bx = 10 |
1
1
|
x |
f(bx) = ebx = e |
1
1
|
x |
f(bx) = |bx| = | |
1
1
|
x| |
f(bx) = log2 (bx) = log2( |
1
1
|
x) |
f(bx) = log(bx) = log( |
1
1
|
x) |
f(bx) = ln(bx) = ln( |
1
1
|
x) |
f(x) = x | |||
|
f(x) = x2 | ||||||
|
f(x) = √ x | |||
|
|
|||||||
|
f(x) = x3 | ||||||
|
|
|||
|
f(x) = 2 x | |||||
|
f(x) = 10 x | |||||
|
f(x) = e x | |||||
|
f(x) = | x | | ||||
|
f(x) = log2 x | ||||||
|
f(x) = log x | ||||||
|
f(x) = ln x | ||||||
|
f(x – | c | ) = x – c | = |
x – |
0
|
f(x – c) = (x – c)2 | = |
(x – |
0
|
)2 |
f(x – c) = √ x – c | = |
x – |
0
|
f(x – c) = |
1
x – c
|
= |
1
|
f(x – c) = (x – c)3 | = |
(x – |
0
|
)3 |
f(x – c) = | = |
x – |
0
|
f(x – c) = 2x – c | = |
2 | x – |
0
|
f(x – c) = 10x – c | = |
10 | x – |
0
|
f(x – c) = ex – c | = |
e | x – |
0
|
f(x – c) = |x – c| | = |
|x – |
0
|
| |
f(x – c) = log2(x – c) | = |
log2(x – |
0
|
) |
f(x – c) = log(x – c) | = |
log(x – |
0
|
) |
f(x – c) = ln(x – c) | = |
ln(x – |
0
|
) |
f(x) = x | |||
|
f(x) = x2 | ||||||
f(x – c) = x2
|
f(x) = √ x | ||
|
|
|||||
|
f(x) = x3 | ||||||
f(x) = x3
|
|
|||
|
f(x) = 2x | ||
|
f(x) = 10x | ||
|
f(x) = ex | ||
|
f(x) = |x| | |||
|
f(x) = log2 x | |||
|
f(x) = log x | |||
|
f(x) = ln x | |||
|
f(x) + d = x + d | = |
x + |
0
|
f(x) + d = x2 + d | = |
x2 + |
0
|
f(x) + d = √ x + d | = |
√ x | + |
0
|
f(x) + d = |
1
x
| + d | = |
1
x
|
+ |
0
|
f(x) + d = x3 + d | = |
x3 + |
0
|
f(x) + d = | + d | = |
+ |
0
|
f(x) + d = 2x + d | = |
2x + |
0
|
f(x) + d = 10x + d | = |
10x + |
0
|
f(x) + d = ex + d | = |
ex + |
0
|
f(x) + d = |x| + d | = |
|x| + |
0
|
f(x) + d = log2(x) + d | = |
log2(x) + |
0
|
f(x) + d = log(x) + d | = |
log(x) + |
0
|
f(x) + d = ln(x) + d | = |
ln(x) + |
0
|
f(x) = x | |||
|
f(x) = x2 | |||
|
f(x) = √ x | ||
|
|
||||
|
f(x) = x3 | |||
|
|
|||
|
f(x) = 2x | |||
|
f(x) = 10x | |||
|
f(x) = ex | |||
|
f(x) = |x| | ||||
|
f(x) = log2(x) | |||
|
f(x) = log(x) | |||
|
f(x) = ln(x) | |||
|
a | f | b | (x – | c | ) | + | d = |
a | b | (x – | c | ) | + | d = |
1
1
|
1
1
|
(x – |
0
|
) | + |
0
|
a | f | b | (x – | c | ) | + | d = |
a | b | (x – | c | ) | 2 | + | d = |
1
1
|
1
1
|
(x – |
0
|
) | 2 | + |
0
|
a | f | b | ( x – | c | ) | + | d = |
a | b | ( x – | c | ) | + | d = |
1
1
|
1
1
|
( x – |
0
|
) | + |
0
|
a | f | b | (x – | c | ) | + | d = |
a |
1
|
+ | d = |
1
1
|
1
|
+ |
0
|
a | f | b | (x – | c | ) | + | d = |
a | b | (x – | c | ) | 3 | + | d = |
1
1
|
1
1
|
(x – |
0
|
) | 3 | + |
0
|
a | f | b | (x – | c | ) | + | d = |
a | b | ( x – | c | ) | + d = |
1
1
|
1
1
|
( x – |
0
|
) | + |
0
|
a | f | b | (x – | c | ) | + | d = |
a | 2 | b | (x – | c | ) | + | d = |
1
1
|
2 |
1
1
|
(x – |
0
|
) | + |
0
|
a | f | b | (x – | c | ) | + | d = |
a | 10 | b | (x – c) | + | d = |
1
1
|
10 |
1
1
|
(x – |
0
|
) | + |
0
|
a | f | b | (x – | c | ) | + | d = |
a | e | b | (x – c) | + | d = |
1
1
|
e |
1
1
|
(x – |
0
|
) | + |
0
|
a | f | b | (x – | c | ) | + | d = |
a | b | (x – | c | ) | + | d = |
1
1
|
1
1
|
(x – |
0
|
) | + |
0
|
a | f | b | (x – | c | ) | + | d = |
a | log2 | b | (x – | c | ) | + | d = |
1
1
|
log2 |
1
1
|
(x – |
0
|
) | + |
0
|
a | f | b | (x – | c | ) | + | d = |
a | log | b | (x – | c | ) | + | d = |
1
1
|
log |
1
1
|
(x – |
0
|
) | + |
0
|
a | f | b | (x – | c | ) | + | d = |
a | ln | b | (x – | c | ) | + | d = |
1
1
|
ln |
1
1
|
(x – |
0
|
) | + |
0
|
f(x) = x | ||||||
|
f(x) = x 2 | |||||||||||
|
f(x) = √ x | ||||||||||
|
|
||||||||||
|
f(x) = x 3 | |||||||||||
|
|
||||||||||
|
f(x) = 2 x | |||||||||
|
f(x) = 10 x | |||||||||
|
f(x) = e x | |||||||||
|
f(x) = | x | | ||||||||||
|
f(x) = log2 x | |||||||||
|
f(x) = log x | |||||||||
|
f(x) = lnx | |||||||||
|